Exercício físico e demência de Alzheimer: uma revisão da literatura especializada - Machado, Nicole Carolina Salvador; Pretto, Rocheli (My University, 2019)
The main objective of the research was to analyze, from 17 scientific articles, a bibliographical review that sought to provide information about the contribution of physical exercise to Alzheimer 's Dementia (AD) patients. This study was characterized as a qualitative, cross-sectional research and a safe material with important information to the public of Physical Education was intended. From this, the research had the purpose of helping health professionals and even people living in the circle of patients with Alzheimer's disease, so that they can have a significant improvement in quality of life through systematized physical activity . The specialized literature shows a number of emotional, cognitive, motor and social benefits when it addresses the regular practice of physical exercises in patients with Alzheimer's dementia. Among them, we can highlight: reduction of the risk of falls; physical exercise increases cerebral blood circulation; stimulates the better functioning of the nervous system; preservation and improvement in cognitive functions; reduction of AD progress in physically active patients; prevention of common mental disorders; progress in social interaction and improvement in the quality of life; increased self-esteem, improved affectivity and mood, improved thinking ability; improvement in motor coordination, perception and memory; decreased rates of depression, anxiety and hospitalizations; seek psychological support to minimize the psychological impacts that the disease brings (sic).
A pesquisa teve por finalidade principal abordar, a partir de 17 artigos científicos, uma revisão bibliográfica que procurou trazer informações sobre a contribuição que o exercício físico proporciona aos portadores da Demência de Alzheimer (DA). Este estudo caracterizou-se como uma pesquisa qualitativa, de cunho transversal e pretendeu-se um material seguro com informações importantes ao público da Educação Física. A partir disso, a pesquisa teve por finalidade auxiliar os profissionais da área da saúde e até mesmo as pessoas do círculo de convivência de portadores da Doença de Alzheimer, para que estes possam ter uma melhora significativa na qualidade de vida por meio da atividade física sistematizada. A literatura especializada aponta inúmeros benefícios de ordem emocional, cognitiva, motora e social quando aborda a prática regular de exercícios físicos em pacientes com demência de Alzheimer. Dentre eles, podemos destacar: diminuição do risco de quedas; o exercício físico aumenta a circulação sanguínea cerebral; estimula o melhor funcionamento do sistema nervoso; preservação e melhora nas funções cognitivas; redução do avanço da DA em pacientes fisicamente ativos; prevenção de transtornos mentais comuns; progresso no convívio social e melhora na qualidade de vida; aumento da autoestima, melhora na afetividade e humor, melhora na capacidade de raciocínio; melhora na coordenação motora, na percepção e memória; diminuição dos índices de depressão, ansiedade e internações; buscar suporte psicológico para minimizar os impactos psicológicos que a doença traz (sic).
Keywords: Exercícios físicos; Alzheimer, Doença de; Envelhecimento